Pengaruh Rasio Keuangan Terhadap Profitabilitas Perbankan (Studi Empiris Pada Bank Yang Terdaftar di BEI Tahun 2014-2017) - Rizka Hidayati; Rochiyati Murniningsih (Universitas Muhammadiyah Magelang, 2021)
This study aims to examine and analyze the effect of capital adequacy ratio, operational cost of operating income, loan to deposite ratio, net interest margin to profitability . The sampling method uses purposive sampling. This research data uses secondary data and hypothesis testing in this study using multiple linear regression. The research sample is 28 banking companies listed on the Indonesian stock exchange periode 2014-2017. The results showed that operational cost of operating income have a positive effect on profitability. While the capital adequacy ratio, loan to deposite ratio, net interest margin has no effect on profitability